The Effectiveness of the Use of the State Civil Apparatus E-Performance System in the Staffing and Human Resource Development Agency of Serdang Bedagai District - Wiradhana, Agung; Ritonga, Syafruddin; Lubis, Maksum Syahri (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effectiveness of using the e-performance system in improving the performance of the State Civil Apparatus (ASN) at the Serdang Bedagai Regency Personnel and Human Resources Development Agency (BKPSDM). The e-performance system is implemented as an instrument of bureaucratic reform to improve transparency, accountability, and efficiency of ASN performance assessment. The research method used is qualitative with a case study approach, involving in-depth interviews, observation, and documentation. The results showed that the implementation of e-performance has a positive impact on productivity and the quality of public services. Obstacles faced include limited technological infrastructure, resistance to change, and a lack of technical training. Recommendations include increasing technological capacity, providing ongoing training, and intensive socialization so that the system can be optimized sustainably.